Critical water quality parameters affecting survival of Labeo rohita (Hamilton) fry during closed system transportation - Das, Pratap Chandra; Mishra, Bibhudatta; Pati, Bikash Kumar; Mishra, Sudhansu Sekhar (Indian Journal of Fisheries, 2015)
Changes in water quality parameters during closed system transport of Labeo rohita fry were studied to identify the critical changes responsible for seed mortality. Fry of L. rohita (2.38 Â± 0.25 g, 44.2 Â± 6.6 mm) were packed in 39 polythene bags and placed on a continuously shaking platform. Water quality changes and fish mortality in the packs were studied for 36 h at every 3 h interval. Marked increase in dissolved oxygen (DO), free carbon dioxide (CO2), total alkalinity, total ammonia nitrogen (TAN) and nitrite-nitrogen (NO2-N) were observed during initial 12 h. Thereafter, most of these parameters remained either consistent or varied in a narrow range up to 27 h, without any significant increase in mortality of fry. However, subsequently during 27-36 h there was significant reduction in dissolved oxygen (< 3.6 mg l-1), increase in CO2 (> 60 mg l-1) and total alkalinity (>120 mg as CaCO3 l-1). Mortality of fry increased significantly during this period which can be attributed to increased stress due to changes in the above water quality parameters.